Motivation behind the choice of nursing as a profession and its determinants — research among students of nursing at the Medical College of the Jagiellonian University - Dziubak, Małgorzata; Motyka, Marek (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. Due to the high expectations of the public towards nurses, it is important to know what the motivation is that drives candidates to choose this profession. Aim of the study. The aim of this study was to characterize the factors determining the choice of nursing as a profession among individuals who undertake this type of training, and to analyse pro-social attitudes and perceived professional image of nurses, which may influence this choice. Material and methods. The study was conducted among 92 first-year students of the first-degree nursing course of the Faculty of Health Sciences at the Jagiellonian University Medical College in Krakow. The survey was completed by means of the diagnostic survey method, the research tool being an original questionnaire developed for the study. Results. Exocentric motivation (typically pro-social) to choose nursing as a profession dominated in the study group, although it was accompanied by endocentric and egocentric motivation. There was a statistically significant, positive correlation between the general pro-social orientation of the students and motivation to choose the nursing profession. There was also a negative and statistically significant correlation between the respondents‘ negative opinions about the nursing profession and pro-social motivation to choose it. Conclusions. The motivation to choose nursing as a profession is predominantly of mixed character, however, the pro- -social motivation prevails over the self-centered one. Higher levels of pro-social motivation occured among those students whose general attitude is focused on social welfare and those who perceived the professional image of nurses as positive. Pro-social motivation should be monitored and stimulated during the course of study.